Enhancing nitric oxide bioavailability via exogen nitric oxide synthase and l-arginine attenuates ischemia-reperfusion-induced microcirculatory alterations - Engel, Holger; Friedrich, Stefanie; Schleich, Christoph; Gebhard, Martha-Maria; Gross, Wolfgang; Germann, Günter; Reichenberger, Matthias (Annals of plastic surgery, 2017)
Background Nitric oxide (NO) is an important cytoprotective agent against ischemia and reperfusion injury (IRI). Enhancing NO bioavailability via exogen NO synthases (NOSs) and L-arginine promotes conversation to NO, circumventing the problem of nonfunctioning NOSs under hypoxic and acidic conditions. In this study, the authors evaluated the therapeutic efficacy of endothelial, inducible and neuronal NOS, and L-arginine on reperfusion-induced microcirculatory alterations and hemodynamic adverse effects in the microvasculature of skeletal muscle. Methods Vascular pedicle isolated rat cremaster model was used that underwent 2 hours of warm ischemia followed by 1 hour of reperfusion. At 30 minutes before ischemia, normal saline (control group with/without ischemia), endothelial-, inducible-, and neuronal NOSs (2 IE) and L-arginine (50 mg/kg BW) were administered systemically (IV). Ischemia-reperfusion-induced microcirculatory alterations were measured after 1 hour of reperfusion. Mean arterial blood pressure and heart frequency were measured throughout the experiment to determine hemodynamic adverse effects. Results The isoforms of NOSs and L-arginine attenuated ischemia-reperfusion-induced vasoconstriction, improved red blood cell velocity, capillary flow, and leukocyte adherence to the endothelium wall. Hemodynamics was stable throughout the experiment.Conclusions Enhancing NO bioavailability via exogen application of NOSs and L-arginine significantly attenuated ischemia-reperfusion-induced microcirculatory alterations in the microvasculature of skeletal muscle. Significant hemodynamic adverse effects were not present, thus demonstrating this approach might be useful for therapeutic intervention. This “pharmacologic preconditioning” could be an easy and effective interventional strategy to uphold conversation of L-arginine to NO under ischemic conditions.